A study on hematological, serum biochemical and microbiological parameters in wild caught rodents (Journal of Laboratory Animal Science, 2021)
Laboratory mice constitute the most popular animal models used in biomedical research today. Like all animals, even  mice housed in ‘barrier’ facilities are prone to infection. Wild mice (Mus musculus) living near vivaria could serve as  a source of infection or infestation in laboratory mouse colonies, although little is known about the prevalence of  infectious diseases in wild mouse. Very few surveys have been conducted on wild rodent populations to determine  the prevalence of viruses and bacteria and also health monitoring of the wild rodents. Pathogens (bacteria, parasites)  often gain entry into colonies through the introduction of infected animals or infected animal products, but viral  dissemination via contaminated fomites or local wild rodents has also been implicated in the spread of disease. Hence,  a preliminary study was undertaken to determine the prevalence of rodent pathogens and health status in wild mouse  populations in and around and Bangalore. The present study revealed that none of the animals tested were positive  for viral pathogens. However, bacterial pathogens and parasites were found in wild caught mice. Hematological and  serum biochemical parameters were comparable to the colony bred anim
Keywords: serum biochemistry; hematology; microbiology; wild rodents